IDENTIFICATION OF SOIL BUGS (PENTATOMIDAE) ON RICE PLANTS (ORYZA SATIVA L.) FROM SOLOK CITY, WEST SUMATRA - Chahyadi, Ennie; Ridha, Irsyad (Universitas Lancang Kuning, 2025)
ABSTRACT: Soil bugs or rice black bugs are one of the insects that like to suck rice plants. These insects suck rice plants in the vegetative and generative phases and have caused huge economic losses. This research aims to identify and study the appropriate of Soil Bugs species from several rice fields in Lubuk Sikarah District, Solok City, West Sumatra. This research uses a sampling method using light traps at night. Morphological identification of rice black bug samples using a light microscope with the weakest magnification (4x10). The results showed that there were five species of soil bugs obtained, namely Scotinophara coarctata, S. zamboanga, S. trifurcata, S. alegria and S. manguindanaoana. Soil bugs are more commonly found in generative rice plants due to the suitability of food and environmental factors. The amount of S. coarctata are the most dominant because it is the most phytophagous of other species of rice black bugs. The characteristics of soil bugs observed were different distance between the ocelli, length of the third and fourth segments on the antennae, shape of the tubercle antiniferous, shape of the anterolateral pronotum, in the amount and shape of longitudinal veins and closed marginal cells in the forewing venation and different shape of abdominal tergit X.